Diagnostic study and campaign life extention of companhia siderúrgica nacional (CSN) # 2 blast furnace hot blast stoves - Silva, Sidiney Nascimento; Marques, Oscar Rosa; Barbosa, Giancarlo Sterhling; Junior, Fernando Vernilli; Longo, Elson [UNESP] (My University, 2008)
Back in 2000, CSN along with DME, conducted a diagnostic study on Hot Blast Stoves # 1, 2 and 3 of Blast Furnace # 2, after 19 years of operation and close to the end of its design campaign - originally set to last for 20 years. The primary purpose of this study was to support the Company's efforts geared toward extending service life as well as paving the way for the general overhaul of such equipment. In light of this study and the post mortem study conducted in 2002 on Hot Blast Stove # 3 Checker Chamber lining, fresh inspection and refractory maintenance techniques were implemented, such as ceramic welding, thermography, endoscopy and use of auxiliary burners during lengthy shutdowns. Changes to lining design were also introduced during the general overhaul. If one just looks at the financial gains resulting from deferring capital expenditure for the general overhaul - extending the campaign, savings to the tune of R$ 14 million were ultimately attained.
Keywords: Blast furnace; Hot blast stove; Refractory